If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + (n + 9) = 21 Reorder the terms: 8 + (9 + n) = 21 Remove parenthesis around (9 + n) 8 + 9 + n = 21 Combine like terms: 8 + 9 = 17 17 + n = 21 Solving 17 + n = 21 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + n = 21 + -17 Combine like terms: 17 + -17 = 0 0 + n = 21 + -17 n = 21 + -17 Combine like terms: 21 + -17 = 4 n = 4 Simplifying n = 4
| Y=2x^3-14x^2+24x | | 4e+9=-63-8e | | 4(w-3)-2=-4(-6w+6)-8w | | (3n-5)(n-6)=0 | | 63-2e=14-9e | | 5-x=10x | | 33=6+3h | | 4e+6=-50-4e | | 5x+3y=182 | | 8+3e=6+e | | 6a+2=7a-1 | | 3e-2=13e-62 | | 9-8g=31 | | -x-8=4x-38 | | xy+2x=300 | | -4-8x+9x=12 | | .33x+10=0.6 | | -6+3y=-15 | | 3e+16=13e-94 | | (2cosx+1)(cosx+1)=0 | | -x^2-4x+32.01=0 | | 60p+50= | | 7u=4u+9 | | (X+7)(x+1)=(x+1) | | 35=-4d+7 | | (x-0.3)+(2x-0.2)+((40+x)-0.25)=274 | | -10(X+1)=8 | | -6x+15=-33 | | 3x-5(x-4)=-8+3x+3 | | 4x-8=4x+-5 | | 45+4x+7+57x=8 | | 2c-4=c+2 |